Microbial Processing of Jellyfish Detritus in the Ocean - Tinta, Tinkara; Zhao, Zihao; Escobar, Alvaro; Klun, Katja; Bayer, Barbara; Amano, Chie; Bamonti, Luca; Herndl, Gerhard J. (Frontiers in Microbiology, 2020)
When jellyfish blooms decay, sinking jellyfish detrital organic matter (jelly-OM), rich in proteins and characterized by a low C:N ratio, becomes a significant source of OM for marine microorganisms. Yet, the key players and the process of microbial jelly-OM degradation and the consequences for marine ecosystems remain unclear. We simulated the scenario potentially experienced by the coastal pelagic microbiome after the decay of a bloom of the cosmopolitan Aurelia aurita s.l. We show that about half of the jelly-OM is instantly available as dissolved organic matter and thus, exclusively and readily accessible to microbes. During a typical decay of an A. aurita bloom in the northern Adriatic Sea about 100 mg of jelly-OM L–1 becomes available, about 44 μmol L–1 as dissolved organic carbon (DOC), 13 μmol L–1 as total dissolved nitrogen, 11 μmol L–1 of total hydrolyzable dissolved amino acids (THDAA) and 0.6 μmol L–1 PO43–. The labile jelly-OM was degraded within 1.5 days (>98% of proteins, ∼70% of THDAA, 97% of dissolved free amino acids and the entire jelly-DOC pool) by a consortium of Pseudoalteromonas, Alteromonas, and Vibrio. These bacteria accounted for >90% of all metabolically active jelly-OM degraders, exhibiting high bacterial growth efficiencies. This implies that a major fraction of the detrital jelly-OM is rapidly incorporated into biomass by opportunistic bacteria. Microbial processing of jelly-OM resulted in the accumulation of tryptophan, dissolved combined amino acids and inorganic nutrients, with possible implications for biogeochemical cycles.